Radical change of Zn speciation in pig slurry amended soil: Key role of nano-sized sulfide particles. (March 2017) - Formentini, Thiago Augusto; Legros, Samuel; Fernandes, Cristovão Vicente Scapulatempo; Pinheiro, Adilson; Le Bars, Maureen; Levard, Clément; Mallmann, Fábio Joel Kochem; da Veiga, Milton; Doelsch, Emmanuel
Abstract: Spreading livestock manure as fertilizer on farmlands is a widespread practice. It represents the major source of heavy metal(loid)s (HM) input in agricultural soils. Since zinc (Zn) is present at high concentrations in manure, it poses special environmental concerns related to phytotoxicity, groundwater contamination, and introduction in the food chain. Therefore, investigations on the fate and behavior of manure-borne Zn, when it enters the soil environment, are necessary to predict the environmental effects. Nevertheless, long-term field studies assessing Zn speciation in the organic waste matrix, as well as within the soil after manure application, are lacking. This study was designed to fill this gap. Using SEM-EDS and XAS analysis, we reported the following new results: (i) ZnS made up 100% of the Zn speciation in the pig slurry (the highest proportion of ZnS ever observed in organic waste); and (ii) ZnS aggregates were about 1-μm diameter (the smallest particle size ever reported in pig slurry). Moreover, the pig slurry containing ZnS was spread on the soil over an 11-year period, totaling 22 applications, and the resulting Zn speciation within the amended soil was analyzed. Surprisingly, ZnS, i.e. the only species responsible for a nearly 2-fold increase in the Zn concentration within the amended soil, was not detected in this soil. Based on SEM-EDS and XAS observations, we put forward the hypothesis that Zn in the pig slurry consisted of nano-sized ZnS crystallites that further aggregated. The low stability of ZnS nanoparticles within oxic and complex environments such as the studied soil was the key explanation for the radical change in pig slurry-borne Zn speciation after long-term amendments. Graphical abstract: Highlights: Zn speciation was assessed in pig slurry and soil after 11 years of amendments. Nano-sized ZnS particles accounted for 100% of the Zn speciation in the pig slurry. ZnS was not detected within the soil, despite Zn accumulation at the soil surface. The low stability of nano-ZnS explained its rapid conversion within the soil. Abstract : Nano-sized ZnS particles accounted for 100% of the Zn speciation in the pig slurry (PS). PS-borne Zn underwent rapid conversion after spreading on the soil and was subsequently bound to soil minerals and OM.